Eficacia de las Proteínas Derivadas de la Matriz del Esmalte Como Coadyuvante En El Tratamiento Quirúrgico De Las Recesiones Gingivales Revisión de la Literatura (2023)
Gingival recessions are undoubtedly one of the main problems for those who go to the dental office, since they often distort an aesthetic and harmonious smile. This pathology is an alteration in which a displacement of the gingival margin occurs, apical to the cement/enamel junction, with exposure of the root surface. Gingival recessions can be localized or generalized and be associated with one or more tooth surfaces. This pathology is caused by a mechanical or physical impact on the gum tissues or indirectly by an inflammatory process that affects them. Depending on their origin, they are divided into triggering and predisposing factors. The treatment of this pathology requires root coverage, for which there are different approaches.